Відповідь:
19x-11y+12=0
Покрокове пояснення:Simplifying
19x + -11y + 12 = 0
Reorder the terms:
12 + 19x + -11y = 0
Solving
12 + 19x + -11y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-12' to each side of the equation.
12 + 19x + -12 + -11y = 0 + -12
Reorder the terms:
12 + -12 + 19x + -11y = 0 + -12
Combine like terms: 12 + -12 = 0
0 + 19x + -11y = 0 + -12
19x + -11y = 0 + -12
Combine like terms: 0 + -12 = -12
19x + -11y = -12
Add '11y' to each side of the equation.
19x + -11y + 11y = -12 + 11y
Combine like terms: -11y + 11y = 0
19x + 0 = -12 + 11y
19x = -12 + 11y
Divide each side by '19'.
x = -0.6315789474 + 0.5789473684y
Simplifying
x = -0.6315789474 + 0.5789473684y
а)2x*9=12, 2x=4/3, x=2/3
б)3x*10=45, 3x=4,5, x=3/2
в)6x*15=72, 6x=24/5, x=4/5
г)18x*13=468, 18x=36, x=2
№61
а)ты наверно не дописала x в конце: 1/5=2:3x. тогда:
3x=10, x=10/3
б)4x*2=21, 4x=10,5, x=21/8
в)50x*21=1225, 50x=175/3, x=7/6
г)38x*16=608, 38x=38, x=1.
Удачи.